The Effect of Cognitive Behavioral Therapy in Reducing Social Anxiety Among Adult Stutters - Kakamad, Karwan Kakabra (Technium Social Sciences Journal, 2021)
Social anxiety is a chronic disorder that affects about half of all people who stutter. As a result, there is a need for individuals with this disorder to be assessed and treated. In adults who stutter, cognitive-behavioral therapy (CBT) has demonstrated success in reducing anxiety symptoms. This study aimed to determine the effectiveness of a cognitive behavior therapy (CBT) program to reduce social anxiety among adults who stutter. This study included 16 participants, (12) male and (4) female. The Liebowitz Social Anxiety Scale (LSAS) was recorded for pre and post intervention in twelve-week CBT program. The findings highlighted the importance of assessing and treating social anxiety among adults who stutter and indicated that the CBT intervention significantly reduced social anxiety among participants in this research.